The Experiences of Maguindanaon Women School Heads in the Armed Conflict Areas - Kabugatan, Elena; Espartero, Helen (JPAIR Multidisciplinary Research, 2025)
In armed conflict-affected communities in Mindanao, there is a shining Maguindanaon heroine in the schools—heads such as herself renewing to illuminate their path through strong leadership amid adversity. This study aims to explore the experiences of Maguindanaon women school heads in armed conflict-affected areas, focusing on their challenges and contributions to education and peace. The research used a phenomenological lens to present the experiences of eight Maguindanaon women school heads. The data was collected and analyzed through in-depth interviews. Thematic analysis was applied to elicit central themes from their lived experiences, contexts, and perceptions of their future. The study reveals that school leaders manage the repercussions of gender discrimination, traditional roles, and armed conflicts; community buy-in has been critical to the sustainability of education, although support is uneven, with various actors upholding restrictive gender norms. Key findings highlighted the need for gender-responsive policies, leadership training, and psychosocial support for women school heads who played significant roles in education, peacebuilding, community resilience, and leadership. Thus, it is concluded that women school heads play a vital role in redesigning leadership dynamics, promoting agency, and steering change within a competitive environment.